Anisotropy and surface morphology of polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene thin layer irradiated with ion beam. Issue 10 (9th August 2022) - Kim, Dong Hyun; Kim, Eun-Mi; Heo, Gi-Seok; Lee, Dong Wook; Oh, Jin Young; Jeong, Hae-Chang; Won, Jonghoon; Seo, Dae-Shik
ABSTRACT: In this study, the surface modification and liquid crystal alignment characteristics of polystyrene- block -poly(ethylene- ran -butylene)- block - polystyrene (SEBS) coated glass substrates were analysed by varying the ion beam irradiation time. For the determination of the liquid crystal alignment characteristics, polarised optical microscopy was observed, and transmittance and pretilt angle were also measured. For the ascertainment of changes on the film surface, atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS) analysis were conducted. AFM analysis showed changes in peaks on the film surface and the formation of wrinkled structures, and XPS analysis showed that the element ratio of the surface and the bonding structure changed, leading to strong dipole-dipole interaction that enhanced liquid crystal alignment characteristics. Notably, ion beam irradiation rendered the surface anisotropic, resulting in the liquid crystal molecules being aligned in one direction, and the orientation was stronger than the effect of the wrinkled structures. Graphical abstract: uf0001